Planning for a sustainable marine future? Marine spatial planning in the German exclusive economic zone of the North Sea. (September 2019) - Aschenbrenner, Marie; Winder, Gordon M.
Abstract: This study re-examines the marine spatial planning (MSP) process for Germany's North Sea exclusive economic zone (EEZ), one of the earliest European examples of MSP. It does so in order to answer whether in this case MSP was an example of post-political planning (Swyngedouw, 2010; Tafon, 2018; Tafon et al., 2018). Building on earlier research (Jay et al., 2012; Kannen, 2014), the analysis adopts a political ecology perspective, and uses a stakeholder analysis and interviews to identify main actors in the MSP process and their interests in and perceptions of the North Sea, its management and the MSP process. The results confirm earlier research that MSP was used strategically to facilitate offshore wind energy development at the expense of other uses. MSP resolved some matters of spatial competition but not all, and solved few underlying conflicts, since these involve deep-seated tensions among diverse actor perceptions of the North Sea and its management. The research finds the German North Sea EEZ remains a politicized environment, in which MSP is a post-political approach to planning. The research highlights inter-agency tensions and politics as further signs that MSP as post-political planning has not eliminated politics in sea management. Highlights: Analyses actor perceptions of and interests in the German North Sea area. Confirms earlier findings of a strategic use of MSP at the expense of some uses. Reveals the German MSP as a post-political approach to planning. MSP solved few underlying conflicts so that the sea remains politicized. Attention must be paid to inter-agency tensions and politics.